Hypothalamic miRNAs: emerging roles in energy balance control - Schneeberger, Marc; Gomez-Valadés, Alicia G.; Ramirez, Sara; Gomis, Ramon; Claret, Marc (Frontiers in Neuroscience, 2015)
The hypothalamus is a crucial central nervous system area controlling appetite, body weight and metabolism. It consists in multiple neuronal types that sense, integrate and generate appropriate responses to hormonal and nutritional signals partly by fine-tuning the expression of specific batteries of genes. However, the mechanisms regulating these neuronal gene programmes in physiology and pathophysiology are not completely understood. MicroRNAs (miRNAs) are key regulators of gene expression that recently emerged as pivotal modulators of systemic metabolism. In this article we will review current evidence indicating that miRNAs in hypothalamic neurons are also implicated in appetite and whole-body energy balance control.